Persconferentie over de campagne "Shell smeer 'em uit Zuid-Afrika". V.l.n.r.: F.Ginwala (ANC), J.Rodenburg, K.Zinn (USA), K.de Pater, J.Wallage - Stegeman, Jan,
Persconferentie over de campagne "Shell smeer 'em uit Zuid-Afrika". V.l.n.r.: F.Ginwala (ANC), J.Rodenburg, K.Zinn (USA), K.de Pater, J.Wallage.